All this and more : a novel - Shepherd, Peng (William Morrow, an imprint of HarperCollinsPublishers, 2024)
From the critically acclaimed, bestselling author of The Cartographers and The Book of M comes an inventive new novel about a woman who wins the chance to rewrite every mistake she's ever made... and how far she'll go to find her elusive "happily ever after." But there's a twist: the reader gets to decide what she does next to change her fate. Meek, play-it-safe Marsh has just turned forty-five, and her life is in shambles. Her career is stagnant, her marriage has imploded, and her teenage daughter grows more distant by the day. Marsh is convinced she's missed her chance at everything--romance, professional fulfillment, and adventure--and is desperate for a do-over. She can't believe her luck when she's selected to be the star of the global sensation All This and More, a show that uses quantum technology to allow contestants the chance to revise their pasts and change their present lives. It's Marsh's only shot to seize her dreams, and she's determined to get it right this time. But even as she rises to become a famous lawyer, gets back together with her high school sweetheart, and travels the world, she begins to worry that All This and More's promises might be too good to be true. Because while the technology is amazing, something seems a bit off....Can Marsh really make her life everything she wants it to be? And is it worth it?